Why Don't Prices Fall in a Recession? Financial Constraints, Investment, and Customer Relations - Charlotte Bucht; Nils Gottfries; Magnus Lundin (Uppsala University, Department of Economics, 2002)
We construct a model of a financially constrained firm making pricing and investment decisions. The firm operates in a market where customers respond slowly to price changes and there are implementation lags in investment (time to build). Our model implies that the markup over marginal cost is counter-cyclical, the product price responds slowly to demand shocks, and quickly to cost shocks, and the price is strongly related to investment. Estimating the decision rules on aggregate data for Swedish industry, we find that the qualitative results are in line with our model.
urn:nbn:se:uu:diva-2243
Keywords: E31; E32; E44; 330; customer market; price rigidity; price equation; investment equation; Preisrigidität; Mark-up Pricing; Real Business Cycle; Schätzung; Schweden